THE USE OF ROLE-PLAYING METHOD IN INCREASING STUDENTS’ LEARNING INTEREST IN ISLAMIC RELIGIOUS EDUCATION AT SMAS ALKHAIRAAT KALUKUBULA - Mahfuza; Rusli Takunas; Mudaimin (Al-Tawjih: Jurnal Pendidikan Islam, 2025)
This research is entitled “The Use of Role-Playing Method in Increasing Students’ Learning Interest in Islamic Education at SMAS Alkhairaat Kalukubula.” This research aims to examine the use of the role-playing method to increase students’ interest in learning in Islamic Education at SMAS Alkhairaat Kalukubula, and to analyze the outcomes of its implementation in enhancing that interest. This research employed a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. The findings show that the implementation of the role-playing method in Islamic Education at SMAS Alkhairaat Kalukubula has been carried out effectively, in accordance with the learning stages: introduction, main activities, and closing activities. Furthermore, the application of this method has been shown to increase students’ interest in learning, as indicated by several indicators, including increased enjoyment, greater interest, improved focus, and greater student involvement during the learning process. The implication of this research was that teachers were expected to continually develop and apply a range of teaching methods, including role-playing. Students are encouraged to be more active and confident in their participation at each stage of the learning process, including role-playing activities, discussions, and question-and-answer sessions. In addition, school principals are expected to support the implementation of innovative teaching methods by providing adequate facilities, allocating sufficient time, and establishing policies that foster an active and creative learning environment